1. Introduction
An arithmetic function
$f:\mathbb {N}\to \mathbb {C}$
is called multiplicative if
$f(1)=1$
and
$f(mn)=f(m)f(n)$
whenever
$\text {gcd}(m,n)=1$
. Let
$\mathcal {M}$
denote the set of complex-valued multiplicative functions.
A set
$E\subseteq \mathbb {N}$
is called an additive uniqueness set of a set of arithmetic functions
$\mathcal {F}$
if
$f\in \mathcal {F}$
is uniquely determined under the condition
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20240824023240704-0526:S0004972724000479:S0004972724000479_eqn1.png?pub-status=live)
For example,
$\mathbb {N}$
and
$\{1\}\cup 2\mathbb {N}$
are trivially additive uniqueness sets of
$\mathcal {M}$
. This concept was first introduced by Spiro [Reference Spiro12] in 1992. She proved that the set of primes is an additive uniqueness set of
$\mathcal {M}_0=\{f\in \mathcal {M} \mid f(p_0)\neq 0 \ \text {for some prime}\ p_0\}$
. Spiro’s work has been extended in many directions.
Let
$k\geq 2$
be a fixed integer. If there is only one function
$f\in \mathcal {F}$
satisfying
$f(x_1+x_2+\cdots +x_k)=f(x_1)+f(x_2)+\cdots +f(x_k)$
for arbitrary
$x_i\in E$
,
$i\in \{1,2,\ldots ,k\}$
, then E is called a k-additive uniqueness set of
$\mathcal {F}$
.
In 2010, Fang [Reference Fang4] proved that the set of primes is a 3-additive uniqueness set of
$\mathcal {M}_0$
. In 2013, Dubickas and Šarka [Reference Dubickas and Šarka3] generalised Fang’s result to sums of an arbitrary number of primes. In 1999, Chung and Phong [Reference Chung and Phong2] showed that the set of positive triangular numbers
$T_n=\tfrac 12n(n+1)$
,
$n\in \mathbb {N}$
, and the set of positive tetrahedral numbers
$ \textit {Te}_n=\tfrac 16n(n+1)(n+2)$
,
$n\in \mathbb {N}$
, are new additive uniqueness sets for
$\mathcal {M}$
and Park [Reference Park10] extended their work to sums of k triangular numbers for
$k\geq 3$
. Park [Reference Park9] proved that the set of nonzero squares is a k-additive uniqueness set of
$\mathcal {M}$
for every
$k\geq 3$
, although it is not a 2-additive uniqueness set (see [Reference Chung1]). Recently, in [Reference Park11], he showed that the set of positive cubes is a k-additive uniqueness set, like the set of positive squares, for multiplicative functions when
$k\ge 3$
.
In 2018, Kim et al. [Reference Kim, Kim, Lee and Park6] proved that the set of nonzero generalised pentagonal numbers
$\mathcal {P}=\{\tfrac 12n(3n-1) \mid n\in \mathbb {Z}, n \ne 0\}$
, is an additive uniqueness set for
$\mathcal {M}$
and the first author [Reference Hasanalizade5] extended their result to sums of k nonzero pentagonal numbers for
$k\geq 3$
. Later, Kim et al. [Reference Kim, Kim, Lee and Park7] showed that the set of positive pentagonal numbers and the set of positive hexagonal numbers
$\mathcal {H}=\{n(2n-1)\,|\, n\in \mathbb {N}\}$
are new additive uniqueness sets for
$\mathcal {M}$
. They also conjectured that among the sets of s-gonal numbers, only the sets of triangular, pentagonal and hexagonal numbers are additive uniqueness sets for
$\mathcal {M}$
.
Let
$\mathcal {O}=\{\mathcal {O}_m=m(3m-2) \mid m\in \mathbb {Z},m\neq 0\}$
be the set of nonzero generalised octagonal numbers. That is,
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20240824023240704-0526:S0004972724000479:S0004972724000479_eqnu2.png?pub-status=live)
The main result of this paper is the following theorem.
Theorem 1.1. Fix
$k\ge 4$
. The set
$\mathcal {O}$
of nonzero generalised octagonal numbers is a k-additive uniqueness set of
$\mathcal {M}$
; that is, if a multiplicative function
$f_k$
satisfies
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20240824023240704-0526:S0004972724000479:S0004972724000479_eqnu3.png?pub-status=live)
for arbitrary
$x_1,\ldots ,x_k\in \mathcal {O}$
, then
$f_k$
is the identity function.
In Sections 2 and 3, we will also show that
$\mathcal {O}$
is neither an additive nor a
$3$
-additive uniqueness set of
$\mathcal {M}$
.
2. Non
$2$
-additive uniqueness
Theorem 2.1. If a multiplicative function
$f_2$
satisfies
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20240824023240704-0526:S0004972724000479:S0004972724000479_eqnu4.png?pub-status=live)
then
$f_2(2) = 2$
and
$f_2(4)$
can be an arbitrary number. For other n, there are two possibilities for
$f_2$
: either
$f_2(n) = n$
or
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20240824023240704-0526:S0004972724000479:S0004972724000479_eqnu5.png?pub-status=live)
Proof. Trivially,
$f_2(2) = 2$
.
Since
$8$
and
$16$
are generalised octagonal numbers and
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20240824023240704-0526:S0004972724000479:S0004972724000479_eqnu6.png?pub-status=live)
if
$f_2(8) \ne 0$
, then
$f_2(3) = 3$
. Then,
$f_2(5) = 5$
from
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20240824023240704-0526:S0004972724000479:S0004972724000479_eqnu7.png?pub-status=live)
Note that
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20240824023240704-0526:S0004972724000479:S0004972724000479_eqnu8.png?pub-status=live)
Thus,
$f_2(8) = 8$
by solving
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20240824023240704-0526:S0004972724000479:S0004972724000479_eqnu9.png?pub-status=live)
Now assume that
$f_2(8) = 0$
. Then,
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20240824023240704-0526:S0004972724000479:S0004972724000479_eqnu10.png?pub-status=live)
Since
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20240824023240704-0526:S0004972724000479:S0004972724000479_eqnu11.png?pub-status=live)
we obtain an equation
$f_2(3)(1+f_2(5)) = 1 + f_2(5)^2$
from
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20240824023240704-0526:S0004972724000479:S0004972724000479_eqnu12.png?pub-status=live)
However, since
$f_2(2) \cdot f_2(3) = 1+f_2(5)$
, we can conclude that
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20240824023240704-0526:S0004972724000479:S0004972724000479_eqnu13.png?pub-status=live)
Note that if a generalised octagonal number is even, then it is divisible by
$8$
. Also, the sum of two odd generalised octagonal numbers is singly even. So we cannot determine
$f_2(4)$
. It can be an arbitrary value.
Now, we have two cases for the values of
$f_2(n)$
for
$n \le 8$
except
$n=4$
:
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20240824023240704-0526:S0004972724000479:S0004972724000479_eqnu14.png?pub-status=live)
Consider the first case. That is, let us show that
$f_2(n)=n$
for all n except for
$4$
. We use induction on n. Suppose that
$f_2(n)=n$
for
$4\neq n<N$
. If N is not a prime power, then
$N=ab$
with
$\text {gcd}(a,b)=1$
and
$f_2(N) = f_2(a) \cdot f_2(b) = ab =N$
by the multiplicativity of
$f_2$
and the induction hypothesis. Thus, we may assume that
$N=p^k$
is a prime power.
If
$N = 2^r$
with
$r \ge 4$
, then
$f_2(N) = N$
from the equations
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20240824023240704-0526:S0004972724000479:S0004972724000479_eqnu15.png?pub-status=live)
and
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20240824023240704-0526:S0004972724000479:S0004972724000479_eqnu16.png?pub-status=live)
since
$3\cdot 2^{r-3}-1 < 2^r$
.
Now, suppose
$N = 3^{2r+1}$
with
$r \ge 1$
. In this case,
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20240824023240704-0526:S0004972724000479:S0004972724000479_eqnu17.png?pub-status=live)
gives
$f_2(3^{2r+1}) \kern1.3pt{=}\kern1.3pt 3^{2r+1}$
. Next, let us consider
$N \kern1.3pt{=}\kern1.3pt 3^{2r}$
with
$r \kern1.3pt{\ge}\kern1.3pt 2$
. Since
${3^2 \kern1.3pt{\equiv}\kern1.3pt -1 \pmod {5}}$
, we have
$3^{2r} = 5m\pm 1$
with m even. Note that
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20240824023240704-0526:S0004972724000479:S0004972724000479_eqnu18.png?pub-status=live)
Since
$\gcd (m,3m+1) = \gcd (m+1,3m+1) = \gcd (3m+1,5m+1) = 1$
, and both of
$4m$
and
$3m+1$
are less than
$5m+1$
, we can conclude that
$f_2(5m+1) = 5m+1$
. Also,
$f_2(5m-1) = 5m-1$
by the same method. Thus,
$f_2(3^{2r}) = 3^{2r}$
.
The final case is
$N = p^r$
with
$p \ne 2,3$
. Note that
$p^r = 6m\pm 1$
with
$m \ge 2$
and
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20240824023240704-0526:S0004972724000479:S0004972724000479_eqn2.png?pub-status=live)
If
$\gcd (8,m) = \gcd (4,3m\pm 1) = \gcd (4,5m\pm 1) = \gcd (3,5m\pm 1)$
, then (*) yields
$f_2(6m\pm 1) = 6m\pm 1$
. However, otherwise, we must split each factor carefully. This part is complicated, so we break it into several cases. The proofs for
$6m+1$
and
$6m-1$
are similar, so we only treat
$6m+1$
.
Case (i).
$8m$
is a power of
$2$
. In this case, letting
$m = 2^r$
,
$8m = 2^{r+3}$
is greater than
$6m+1$
. So, we cannot apply the induction hypothesis to
$f_2(8m)$
. However, note that
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20240824023240704-0526:S0004972724000479:S0004972724000479_eqnu19.png?pub-status=live)
and
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20240824023240704-0526:S0004972724000479:S0004972724000479_eqnu20.png?pub-status=live)
Thus,
$f_2$
fixes
$2^{r+3} = 8m$
.
Case (ii).
$4(3m+1)$
is a power of
$2$
. If we let
$3m+1 = 2^r$
, then
$4(3m+1) = 2^{r+2}$
and
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20240824023240704-0526:S0004972724000479:S0004972724000479_eqnu21.png?pub-status=live)
However, in this equation,
$2^{r+1} = 2(3m+1)$
is not less than
$6m+1$
. So, we apply this method again to verify
$f_2(2^{r+1}) = 2^{r+1}$
.
Case (iii). The divisor
$4(5m+1)$
of
$12m(5m+1)$
is a power of
$2$
. We can show that
$f_2(4(5m+1)) = 4(5m+1)$
by applying the previous method twice.
Case (iv). The divisor
$3(5m+1)$
of
$12m(5m+1)$
is a power of
$3$
. Since
$\operatorname {ord}_5{3} = 4$
, we have
$3(5m+1) = 3^{4r+1}$
. Thus,
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20240824023240704-0526:S0004972724000479:S0004972724000479_eqnu22.png?pub-status=live)
We can conclude that
$f_2$
fixes
$3(5m+1)$
.
Case (v).
$4(5m+1) = 2^{a+2}\cdot 3$
with
$a \ge 1$
. Since
$\tfrac 134(5m+1)> 6m+1$
, we should check this case. Note that
$5m+1$
is divisible by
$2\cdot 3$
when
$m = 6n+1$
with
$n \ge 1$
. Then,
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20240824023240704-0526:S0004972724000479:S0004972724000479_eqnu23.png?pub-status=live)
If we take both sides modulo
$5$
, we deduce that
$a-1 = 4k$
. That is,
$5n = 16^k-1$
with
$k \ge 1$
. Calculating
$6m+1$
:
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20240824023240704-0526:S0004972724000479:S0004972724000479_eqnu24.png?pub-status=live)
Thus,
$6m+1$
cannot be a power of a prime.
Case (vi).
$3(5m+1) = 2\cdot 3^{b+1}$
with
$b \ge 1$
. Note that
$\tfrac 123(5m+1)> 6m+1$
. However,
$m = 6n+1$
with
$n \ge 1$
. Then,
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20240824023240704-0526:S0004972724000479:S0004972724000479_eqnu25.png?pub-status=live)
and thus
$5n = 3^{4k} - 1$
with
$k \ge 1$
. Thus,
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20240824023240704-0526:S0004972724000479:S0004972724000479_eqnu26.png?pub-status=live)
and this cannot be a power of p.
From (*) and Cases (i)–(vi), we can conclude that
$f_2(6m+1) = 6m+1$
. Similarly,
$f_2$
also fixes
$6m-1$
. Hence,
$f_2(n) = n$
except for
$n=4$
.
By the same process, we can deduce the alternative with
$f_2(2^r) = 0$
for
$r \ge 3$
and
$f_2(n) = 1$
if n is odd.
3. Non
$3$
-additive uniqueness
Theorem 3.1. If a multiplicative function
$f_3$
satisfies
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20240824023240704-0526:S0004972724000479:S0004972724000479_eqnu27.png?pub-status=live)
for
$a,b,c\in \mathcal {O}$
, then
$f_3(n)=n$
for
$n\neq 4$
, and
$f_3(4)$
can be an arbitrary number.
Proof of Theorem 3.1.
Trivially,
$f_3(3) = 3$
. Note that
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20240824023240704-0526:S0004972724000479:S0004972724000479_eqnu28.png?pub-status=live)
If we set
$a = f_3(5)$
, then
$a(a+2) = 3(2a+1)+2$
. We obtain two solutions
$a = -1$
and
$a = 5$
.
If
$f_3(5) = -1$
, then
$f_3(8) = 2$
from
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20240824023240704-0526:S0004972724000479:S0004972724000479_eqnu29.png?pub-status=live)
However, this leads to a contradiction:
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20240824023240704-0526:S0004972724000479:S0004972724000479_eqnu30.png?pub-status=live)
Thus, we can conclude that
$f_3(5)=5$
. Then
$f_3(n)=n$
for
$n\le 8$
except
$n=4$
. We can also find
$f(9) = 9$
and
$f(16) = 16$
from
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20240824023240704-0526:S0004972724000479:S0004972724000479_eqnu31.png?pub-status=live)
Let us show that
$f_3(n)=n$
for all n except
$n=4$
. We use induction on n. Suppose that
$f_3(n)=n$
for
$4\neq n<N$
. If N is not a prime power, then
$N=ab$
with
$\text {gcd}(a,b)=1$
and
$f_3(N)=N$
by the multiplicativity of
$f_3$
and the induction hypothesis. Thus, we may assume that N is a prime power.
If
$N=3^r$
, then from the equalities
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20240824023240704-0526:S0004972724000479:S0004972724000479_eqnu32.png?pub-status=live)
we conclude that
$f_3(3^r)=3^r$
since
$f_3(3^r-2)=3^r-2$
by the induction hypothesis.
Now suppose that
$N=2^{2s+1}$
with
$s\ge 2$
. In this case,
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20240824023240704-0526:S0004972724000479:S0004972724000479_eqnu33.png?pub-status=live)
yields
$f_3(2^{2s+1})=2^{2s+1}$
since
$3\cdot 2^{s-1}-1<2^{2s+1}$
,
$3\cdot 2^s+1<2^{2s+1}$
. Next, assume that s is even and
$N=2^{s+2}$
with
$s\ge 4$
. In this case, from
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20240824023240704-0526:S0004972724000479:S0004972724000479_eqnu34.png?pub-status=live)
we have
$f_3(2^{s+2})=2^{s+2}$
since
$3\cdot 2^{s-2}\pm 1<2^{s+2}$
,
$3\cdot 2^s-1<2^{s+2}$
and
$27\cdot 2^{s-3}-1<2^{s+2}$
.
Now consider
$N = p^r$
with
$p \ne 2,3$
. Assume
$N = p^r = 6m-1$
with
$m \ge 1$
and
$f_3(n) = n$
for all
$n < N$
.
Note that
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20240824023240704-0526:S0004972724000479:S0004972724000479_eqnu35.png?pub-status=live)
To calculate
$f_3(6m-1)$
, we consider two cases.
Case (i). m is odd. In this case,
$\gcd (m,3m-2) = \gcd (2,m) = \gcd (m,9m-2) = 1$
and every factor of the above two equations is less than
$6m-1$
except
$9m-2$
or a power of
$2$
or
$3$
. So, letting
$x = f_3(6m-1)$
and
$y = f_3(9m-2)$
, we can write
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20240824023240704-0526:S0004972724000479:S0004972724000479_eqnu36.png?pub-status=live)
and these equations yield
$x = f_3(6m-1) = 6m-1$
and
$y = f_3(9m-2) = 9m-2$
.
Case (ii). m is even. Let
$m = 2n$
. Then, we should check
$f_3(12n-1)$
. Note that
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20240824023240704-0526:S0004972724000479:S0004972724000479_eqnu37.png?pub-status=live)
and
$\gcd (n,3n-1) \kern1.4pt{=}\kern1.4pt \gcd (2,12n-1) \kern1.4pt{=}\kern1.4pt \gcd (n,12n-1) \kern1.4pt{=}\kern1.4pt \gcd (n,9n-1) \kern1.4pt{=}\kern1.4pt 1$
, and every factor is less than
$12n-1$
or a power of
$2$
or
$3$
. However, we have an exceptional case to check:
$16n$
is a power of
$2$
greater than
$12n-1$
. In this case, we can use the equalities for
$f_3(2^r)$
. So,
$f_3$
fixes every factor. Thus, if we rearrange the equality
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20240824023240704-0526:S0004972724000479:S0004972724000479_eqnu38.png?pub-status=live)
we obtain
$f_3(6m-1) = f_3(12n-1) = 12n-1$
.
For the case
$N = p^r = 6m+1$
, we can use
$\mathcal {O}_{-m} = m(3m+2)$
.
4.
$4$
-additive uniqueness
Theorem 4.1. If a multiplicative function
$f_4$
satisfies
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20240824023240704-0526:S0004972724000479:S0004972724000479_eqnu39.png?pub-status=live)
for
$a,b,c,d\in \mathcal {O}$
, then
$f_4$
is the identity function.
We will need the following lemma.
Lemma 4.2 (Kim et al. [Reference Kim, Lee and Oh8, Theorem 4.7]).
For any integer
$k\ge 4$
, any positive integer n is a sum of k nonzero generalised octagonal numbers, except for
$n=1,2,\ldots ,k-1$
and
$k+b$
, where
$b\in B=\{1,2,3,5,6,9,10,13,17\}$
.
Proof of Theorem 4.1.
By Lemma 4.2, every positive integer can be represented as a sum of four nonzero generalised octagonal numbers except for
$1,2,3,5,6,7,9,10,13$
,
$14,17,21$
. Note that it is sufficient to determine
$f_4(n)$
for
$n=2,3,5,7,9,13,17$
.
Trivially,
$f_4(1)=1$
and
$f_4(4)=4$
. Note that
$f_4(12)=4f_4(3)=f_4(5+5+1+1)=2f_4(5)+2$
. Thus,
$f_4(3)=\tfrac 12(f_4(5)+1)$
. Moreover,
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20240824023240704-0526:S0004972724000479:S0004972724000479_eqnu40.png?pub-status=live)
Now observe that
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20240824023240704-0526:S0004972724000479:S0004972724000479_eqnu41.png?pub-status=live)
After simplification,
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20240824023240704-0526:S0004972724000479:S0004972724000479_eqnu42.png?pub-status=live)
For convenience, let
$f_4(5)=a$
. Then
$2a^2+4a=(a+1)(a+6)+4$
and we obtain two solutions
$f_4(5)=-2$
and
$f_4(5)=5$
. The first solution yields
$f_4(3)=-\tfrac 12$
and
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20240824023240704-0526:S0004972724000479:S0004972724000479_eqnu43.png?pub-status=live)
However, this leads to a contradiction:
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20240824023240704-0526:S0004972724000479:S0004972724000479_eqnu44.png?pub-status=live)
Thus, we can conclude that
$f_4(3)=3$
,
$f_4(5)=5$
and
$f_4(7)=7$
. Since
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20240824023240704-0526:S0004972724000479:S0004972724000479_eqnu45.png?pub-status=live)
we find
$f_4(2)=2$
,
$f_4(9)=9$
,
$f_4(13)=13$
and
$f_4(17)=17$
.
Since other numbers can be expressed as sums of four positive generalised octagonal numbers, we can conclude that
$f_4$
is the identity function by induction.
5.
$5$
-additive uniqueness
Theorem 5.1. If a multiplicative function
$f_5$
satisfies
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20240824023240704-0526:S0004972724000479:S0004972724000479_eqnu46.png?pub-status=live)
for
$a,b,c,d,e\in \mathcal {O}$
, then
$f_5$
is the identity function.
Proof of Theorem 5.1.
By Lemma 4.2, the exceptional set is
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20240824023240704-0526:S0004972724000479:S0004972724000479_eqnu47.png?pub-status=live)
Note that
$f_5(5)=5$
and
$f_5(9)=f_5(5+1+1+1+1)=f_5(5)+4=9$
. So it is sufficient to determine
$f_5(n)$
for
$n=2,3,4,7,8,11$
. Note that
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20240824023240704-0526:S0004972724000479:S0004972724000479_eqnu48.png?pub-status=live)
Then
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20240824023240704-0526:S0004972724000479:S0004972724000479_eqnu49.png?pub-status=live)
Therefore,
$f_5(8)=8$
and from
$f_5(24)=f_5(3) \cdot f_5(8)=f_5(8+5+5+5+1)= 16+f_5(8)$
, we get
$f_5(3)=3$
. Similarly, from
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20240824023240704-0526:S0004972724000479:S0004972724000479_eqnu50.png?pub-status=live)
we deduce that
$f_5(2)=2$
,
$f_5(4)=4$
,
$f_5(7)=7$
and
$f_5(11)=11$
, respectively.
Since other numbers can be represented as sums of five positive generalised octagonal numbers, we can conclude that
$f_5$
is the identity function by induction.
6. Proof for k-additivity with
$k\ge 6$
Let
$k\geq 6$
and
$f_k$
be k-additive on positive generalised octagonal numbers. That is,
$f_k(x_1+x_2+\dotsb +x_k)=f_k(x_1)+f_k(x_2)+\dotsb +f_k(x_k)$
for arbitrary
$x_1,\ldots ,x_k\in \mathcal {O}$
. Trivially,
$f_k(1)=1$
and
$f_k(k)=k$
.
Note that
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20240824023240704-0526:S0004972724000479:S0004972724000479_eqnu51.png?pub-status=live)
Let
$x=f_k(5)$
,
$y=f_k(8)$
,
$z=f_k(16)$
and
$w=f_k(21)$
. The above equalities give rise to the system of equations
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20240824023240704-0526:S0004972724000479:S0004972724000479_eqnu52.png?pub-status=live)
The solutions are
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20240824023240704-0526:S0004972724000479:S0004972724000479_eqnu53.png?pub-status=live)
Consider the first solution set
$f_k(5)=f_k(8)=f_k(16)=f_k(21)=1$
. Arrange the positive generalised octagonal numbers into an increasing sequence and let
$O_n$
denote the nth term. Then
$f_k(O_1)=f_k(O_2)=f_k(O_3)=f_k(O_4)=f_k(O_5)=1$
. As seen in Section 5, every
$O_n$
with
$n\geq 6$
can be written as a sum of five positive generalised octagonal numbers. From the equality
![](https://static.cambridge.org/binary/version/id/urn:cambridge.org:id:binary:20240824023240704-0526:S0004972724000479:S0004972724000479_eqn3.png?pub-status=live)
with
$a,b,c,d,e<f$
, we infer that
$f_k(O_n)=1$
for all
$n\geq 6$
inductively. However, for sufficiently large n,
$O_n$
can be represented as a sum of k positive generalised octagonal numbers. So
$f_k(O_n)=k$
, which is a contradiction.
Hence, we conclude that
$f_k(5)=5$
,
$f_k(8)=8$
,
$f_k(16)=16$
and
$f_k(21)=21$
. Moreover, (6.1) yields
$f_k(O_n)=O_n$
for every
$n\geq 1$
.
If N is a sum of k positive generalised octagonal numbers, then
$f_k(N)=N$
. Otherwise, choose an integer
$M>k+17$
such that
$\text {gcd}(M,N)=1$
. Then M and
$MN$
can be represented as sums of k positive generalised octagonal numbers by Lemma 4.2. By the multiplicativity of
$f_k$
,
$Mf_k(N)=f_k(M) \cdot f_k(N)=f_k(MN)=MN$
. Therefore,
$f_k(N)=N$
and this completes the proof.